2022
DOI: 10.2174/0929866529666220825150025
|View full text |Cite
|
Sign up to set email alerts
|

Modified Levels of Renin Angiotensin Related Components in the Frontal Cortex and Hippocampus were Associated with Neuroinflammation and Lower Neuroprotective Effects of NGF During Acute Hepatic Encephalopathy in Mice

Abstract: Background: Hepatic encephalopathy (HE) is a neuropsychiatric syndrome that involves cognitive and motor dysfunctions due to hepatic failure. Clinical and experimental studies suggest that the angiotensin (Ang) converting enzyme (ACE), Ang II, and angiotensin type 1 receptor (AT1R), that compose the classical pathway of the renin–angiotensin system (RAS), exacerbate neuroinflammation in different neurologic diseases. Conversely, Ang-(1-7), ACE2, and Mas receptor, which integrate the alternative RAS axis, have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…These results suggested that upregulation of BDNF and NGF levels may contribute to the protection of nicorandil against cognitive dysfunction after TBI. Previous studies also reveal that BDNF/NGF downregulates cellular oxidative stress and inflammation during brain injury (Oliveira et al, 2022;Scotton et al, 2020), implying the possible involvement of BDNF and NGF in the antioxidative stress and anti-inflammation of nicorandil.…”
Section: Discussionmentioning
confidence: 91%
“…These results suggested that upregulation of BDNF and NGF levels may contribute to the protection of nicorandil against cognitive dysfunction after TBI. Previous studies also reveal that BDNF/NGF downregulates cellular oxidative stress and inflammation during brain injury (Oliveira et al, 2022;Scotton et al, 2020), implying the possible involvement of BDNF and NGF in the antioxidative stress and anti-inflammation of nicorandil.…”
Section: Discussionmentioning
confidence: 91%
“… 50 51 52 In mice, Oliveira et al showed elevated levels of IFN-γ and CCL2 in the prefrontal cortex and of TNF, IL-6, IL-12, and CCL2 in the hippocampus of TAA-treated animals. 53 Alongside these data, TAA intoxication was associated with microglial and astroglial activation. 54 Briefly, acute injection of TAA leads to liver injury, impairing the elimination of blood toxins, such as ammonia and lipopolysaccharides.…”
Section: Hyperammonemia and Inflammation In Hepatic Encephalopathymentioning
confidence: 81%